If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16t(t + 1)(t + -5) = 0 Reorder the terms: -16t(1 + t)(t + -5) = 0 Reorder the terms: -16t(1 + t)(-5 + t) = 0 Multiply (1 + t) * (-5 + t) -16t(1(-5 + t) + t(-5 + t)) = 0 -16t((-5 * 1 + t * 1) + t(-5 + t)) = 0 -16t((-5 + 1t) + t(-5 + t)) = 0 -16t(-5 + 1t + (-5 * t + t * t)) = 0 -16t(-5 + 1t + (-5t + t2)) = 0 Combine like terms: 1t + -5t = -4t -16t(-5 + -4t + t2) = 0 (-5 * -16t + -4t * -16t + t2 * -16t) = 0 (80t + 64t2 + -16t3) = 0 Solving 80t + 64t2 + -16t3 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), '16t'. 16t(5 + 4t + -1t2) = 0 Factor a trinomial. 16t((5 + -1t)(1 + t)) = 0 Ignore the factor 16.Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0Subproblem 2
Set the factor '(5 + -1t)' equal to zero and attempt to solve: Simplifying 5 + -1t = 0 Solving 5 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1t = 0 + -5 -1t = 0 + -5 Combine like terms: 0 + -5 = -5 -1t = -5 Divide each side by '-1'. t = 5 Simplifying t = 5Subproblem 3
Set the factor '(1 + t)' equal to zero and attempt to solve: Simplifying 1 + t = 0 Solving 1 + t = 0 Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + t = 0 + -1 Combine like terms: 1 + -1 = 0 0 + t = 0 + -1 t = 0 + -1 Combine like terms: 0 + -1 = -1 t = -1 Simplifying t = -1Solution
t = {0, 5, -1}
| 2x+4(x-5)=2(x-4) | | 8m-11+2m-4=180 | | -x+3+14x=-6+4x+36 | | 2x+6-x-3=40 | | 0.09x+0.19(x+7000)=3570 | | (3x-3)=48 | | 3x^2-2y=48 | | (3x-3)=58 | | 2x^2+3x-23=3 | | 5b-22=7b+12 | | 4x-5(2x+1)=6x+1 | | 4x-5(2x+1)=-6x+5 | | 0.3(x+-100000)=1000000 | | 4x-5(2x+1)=1x+-5 | | 38ln(x)=79 | | 38lnx=79 | | 4x-5(2x+1)=0x+-5 | | -(3x-5)-(5x-2)+4=-8(x-4)-(3x+4)+4 | | 4x-5(2x+1)=-0x+-5 | | x^2y+4y+5x^2+20= | | -12=-7u | | 4x-5(2x+1)=-6x+0 | | 8y+11=2y+2d+7 | | 20x+4=4(5x+1)-x+4 | | 3(3x+4)-5=-3x+4 | | 3(3x+4)-5=9x+-2 | | 1,3,5,7,11,13,15=30 | | 3(3x+4)-5=-3x+-5 | | -248=c-108 | | -15-x=-24 | | 12*14= | | -11k^2-34k+1=0 |